Stainless‐steel wires exclude gulls from a wastewater treatment plant. Issue 10 (1st October 2013) - Clark, Daniel E.; Koenen, Kiana K.G.; Mackenzie, Kenneth G.; Pereira, Jillian W.; Destefano, Stephen
Abstract : There is growing concern about the prevalence of pathogens and antibiotic‐resistant bacteria in the environment and the role wildlife plays in their transmission and dissemination. Gulls feeding at wastewater treatment plants may provide a route for transmission of pathogens and bacteria to public water supplies or other critical areas. The authors identified gulls routinely feeding at a wastewater treatment plant in Millbury, Mass., and tested the effectiveness of overhead stainless‐steel wires in excluding gulls from the plant. The number of gulls in certain structures was compared before and after wiring and during an experimental approach using simultaneous treatments and controls. Stainless‐steel wires spaced at 0.9–3.3 m (3–10 ft) effectively prevented gulls from using treatment structures ( p < 0.0001) and were effective for > 24 months. Materials costs to wire all structures was about $5, 700, and labor costs were $4, 020. Overhead stainless‐steel wires can provide a long‐term, cost‐efficient method of excluding ring‐billed gulls from wastewater treatment plants.